The foundations of cooperation: building cartels in the Nordic cement industry and beyond, 1890–1947. Issue 3 (1st September 2020) - Dahlström, Malin
ABSTRACT: Cooperation and cartels are common-place in the cement industry. The Nordic countries' close historical ties meant cooperation between the cement companies and their directors existed from the industry's establishment in the 1890s. Cooperation was an essential part of the activities of cement company managers and was integral to business operations, with national cartels also establishing international cartels. While cooperation was ever present, its forms varied over time. Even when the form and membership of the cartels changed, however, exports were always central. Cartel agreements were re-negotiated regularly and their Nordic managers kept in close contact with each other. The Nordic cement producers also cooperated with other European producers, eventually leading to the establishment of a European cement cartel, the Cembureau, in 1947. The Cembureau was the ultimate result of a long period of cooperation and trust driven by the Nordic cement companies.